El clima escolar y el estrés académico de los estudiantes de bachillerato de la unidad educativa fiscomisional monseñor Alberto Zambrano Palacios, cantón Olmedo periodo 2013– 2014 - Ramírez Cuenca, Laura Elizabeth (2015)
The present research work entitled: The school climate and academic stress of the students from Bachillerato at “Monseñor Alberto Zambrano Palacios” Fiscomisional Educative Unit, Olmedo Canton, Academic Period 2013 – 2014, was established with the purpose of analyzing the influence of the school climate on the academic stress of the researched students. It was a descriptive study with 70 students from Bachillerato at “Monseñor Alberto Zambrano Palacios” Fiscomisional Educative Unit, Olmedo Canton. The methods used for the research were scientific, statistical, descriptive, analytical, synthetic, deductive, and inductive. The survey “The climate scale perception and the academy performance (Gardner, 2008) and SISCO Inventory of Academic Stress Barraza Arturo Macias (2007)” was used. 54% of the regarding results about the school climate demonstrate that standards and values are in a low level, while 91% demonstrate the academic stress in a deep level regarding stressors such as class participation, expositions, subjects they study become disquieting situations; 78% with a moderate level present physical, psychological and behavioral symptoms. Conclusions: Most of the students perceive the school climate (standards and values) in a low level, while the academic stress is demonstrated in a deep level, which are the stressors. In this research population standards and values influence on a deep level of academic stress (stressors)